ESCOLANO BENITO, A. (2001). "El pensil de las niñas". Madrid, México, Buenos Aires, San Juan: Edaf - Rufino Cano González (Universidad de La Rioja, 2013)
ESCOLANO BENITO, A. (2001). El pensil de las niñas. Madrid, México, Buenos Aires, San Juan: Edaf.